PENDEKATAN SCIENTIFIC BERBASIS LESSON STUDY DALAM PEMBELAJARAN TEMATIK TERPADU KONTEKS PENINGKATAN PROFESIONALITAS GURU - Nuryanto Nuryanto (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
The professionalism of Teachers’ performance need to be improved continuosly especially in the implementation of the 2013 curriculum, which was also implemented on learning in primary school. Scientific approach is a learning process that is stated in implementing the 2013 curriculum and highly recommended to be applied in all learning aspects. In order that, Lesson Study (LS) which has some phases such as 1) planning (Plan), 2) implementation (Do) and, 3) reflection (See), can be used to improve the quality of teacher performance that impact on the quality of students in learning processes and outcomes. In practice, through the implementation of Lesson study can improve the theachers’ abilities in four competencies, they are pedagogical, personality, professional and social ability.